What is The Effectiveness of Intravenous Magnesium Supplementation Compared to Standard Care on Clinical Outcomes in Critically Ill Patients with Hypomagnesemia? : A Systematic Review - Landong Sijabat; Raka Jati Prasetya; Mutia Juliana (International Medical Journal Corp. Ltd, 2026)
Introduction: Hypomagnesemia is common in critically ill patients and is associated with adverse outcomes. However, the effectiveness of intravenous (IV) magnesium supplementation remains controversial. Methods: This systematic review screened 80 studies including RCTs, etc across general ICUs, cardiac surgery, sepsis, neurological conditions, and other critical illnesses. Outcomes assessed included mortality, arrhythmias, neurological recovery, length of stay, and adverse events. Results: In post-cardiac surgery, IV magnesium significantly reduced supraventricular arrhythmias (RR 0.77; 95% CI: 0.63–0.93) and ventricular arrhythmias (RR 0.52; 95% CI: 0.31–0.87) [1,2]. In sepsis, magnesium improved lactate clearance and reduced ICU stay from 15 to 8 days (p<0.01) [3], with a network meta-analysis showing reduced short-term mortality (RR 0.33; 95% CI: 0.14–0.79) [4]. In AKI on CRRT, magnesium was associated with significantly lower 90-day mortality (aHR 0.38; 95% CI: 0.18–0.83) [5]. In aneurysmal SAH, magnesium reduced vasospasm (OR 0.61; 95% CI: 0.37–0.99) and delayed cerebral ischemia (OR 0.57; 95% CI: 0.37–0.88) but did not improve overall neurological outcome [6,7]. In TBI, the largest RCT showed no benefit and potential harm [8]. In general ICU patients with borderline hypomagnesemia, routine supplementation did not improve 24-hour clinical outcomes [9]. Extended infusion strategies improved magnesium retention compared to rapid boluses [11,12]. Adverse events were generally mild, though higher doses in TBI increased mortality [8]. Discussion: The effectiveness of IV magnesium is highly context-dependent. Strongest evidence supports arrhythmia prevention post-cardiac surgery. Sepsis and AKI on CRRT show promising signals for mortality and organ function, but evidence certainty is low. Neurological benefits are limited to intermediate events without improving final outcomes. Routine supplementation for mild hypomagnesemia in general ICU is not supported. Conclusion: IV magnesium supplementation is recommended for arrhythmia prophylaxis in post-cardiac surgery. Its role in sepsis and AKI on CRRT requires further high-quality RCTs. Magnesium should not be routinely administered for mild hypomagnesemia in general ICU or for neuroprotection in TBI.